2002
DOI: 10.1046/j.1525-1438.2002.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Gd-DTPA contrast-enhanced dynamic MRI and serum determination of LDH and its isozymes in the differential diagnosis of leiomyosarcoma from degenerated leiomyoma of the uterus

Abstract: This prospective study was conducted to identify the magnetic resonance imaging (MRI) characteristics of uterine leiomyosarcoma (LMS) and to evaluate the diagnostic accuracy of conventional MRI and dynamic MRI with or without serum measurement of lactate dehydrogenase (LDH) levels. Two hundred ninety-eight consecutive patients were entered in this study. In eligible 227 patients, ten patients with LMS and 130 patients with uterine degenerated leiomyoma (DLM) were included for the present study. Precontrast T1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(167 citation statements)
references
References 20 publications
2
161
0
2
Order By: Relevance
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…represent another criterion in the differential diagnosis between sarcomas and uterine leiomyomas, because it has been demonstrated that sarcomas show an intense and avid enhancement with respect to the benign formations [27][28][29] . In addition, in the post-processing it was possible to process the captured images through subtraction and calculation of time-intensity curves.…”
Section: Mri Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of Positron Emission Tomography/Computed Tomography (PET/CT) to differentiate ordinary leiomyomas, leiomyomas variants, and leiomyosarcomas remains limited because ordinary leiomyomas can take up Fluorodeoxyglucose (FDG) on PET (as a marker for cellular proliferation) [33]. It is still difficult to accurately determine uterine sarcoma from STUMP tumors or cellular leiomyoma [29][30][31][32][33].…”
Section: E Atypical Leiomyomamentioning
confidence: 99%
“…It is still difficult to accurately determine uterine sarcoma from STUMP tumors or cellular leiomyoma [29][30][31][32][33].…”
Section: E Atypical Leiomyomamentioning
confidence: 99%